Mudança de concepção das políticas públicas para o campo brasileiro: o Programa de Aquisição de Alimentos, PAA - de Medeiros Hespanhol, Rosangela Ap. [UNESP] (Univ Barcelona, Dept Geografia Humana, 2008)
In the 90, the public politics for the Brazilian rural way incorporated the territorial perspective, besides they motivate the participation and the beneficiaries collective organization. In 2003 the Food Acquisition Program (FAP) was created with the intention of guaranteeing the feeding of people in social vulnerability situation or alimentary insecurity and of providing work and income in the field through the direct buying of the agriculturists foods. In a research made in two São Paulo State's towns: Tupi Paulista and Dracena, it was verified that the price paid to the farmers is higher to the regional average and because of this fact the participants have interest in enlarging the cultivated area and/or in diversifying the cultivations. Though, two problems were detected: 1) the reduced number of beneficiated producers; and, ii) the furtherance of the producers relatives already registered that try to increase their quota of products and the value to be received.
Change of the public politics conception for Brazilian fiel: the food acquisition program, PAA
Keywords: Public politics; commercialization; job providing and income; rural space